2018
DOI: 10.1038/s41431-018-0299-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of recessive inheritance in early-onset epileptic encephalopathies: a combined whole-exome sequencing and copy number study

Abstract: Early-onset epileptic encephalopathy (EE) and combined developmental and epileptic encephalopathies (DEE) are clinically and genetically heterogeneous severely devastating conditions. Recent studies emphasized de novo variants as major underlying cause suggesting a generally low-recurrence risk. In order to better understand the full genetic landscape of EE and DEE, we performed high-resolution chromosomal microarray analysis in combination with whole-exome sequencing in 63 deeply phenotyped independent patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 58 publications
1
56
0
5
Order By: Relevance
“…A further 19 articles were identified from additional sources, not included in the initial search numbers. This included five articles which were full text versions of conference abstracts [38][39][40][41][42]. One paper returned in the initial search published through TCGA [43], led to the identification of a further 13 articles on multi-omics of rare cancers [44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A further 19 articles were identified from additional sources, not included in the initial search numbers. This included five articles which were full text versions of conference abstracts [38][39][40][41][42]. One paper returned in the initial search published through TCGA [43], led to the identification of a further 13 articles on multi-omics of rare cancers [44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: Resultsmentioning
confidence: 99%
“…3). Two of the final 66 included papers were published in 2019, despite the 2018 date restriction, as these were identified from within the additional TCGA search [38,59]. Evolution of inclusion and exclusion criteria is not unusual within the process of conducting scoping reviews [37].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mostly, dominant acting, de novo mutations have been identified in children suffering from DEEs 3 , and only a limited number of genes with a recessive mode of inheritance are known so far, with a higher occurrence rate in consanguineous populations 4 . A recent cohort study on DEEs employing whole exome sequencing (WES) and copy-number analysis, however, found that up to 38% of diagnosed cases might be caused by recessive genes, indicating that the importance of this mode of inheritance in DEEs has been underestimated 5 .…”
Section: Introductionmentioning
confidence: 99%
“…A substantial number of DEE patients have been shown to have an underlying genetic etiology, with de novo heterozygous variants playing an important role . With rapid advancements in molecular biology and genetic techniques, >100 genes have been associated with DEEs in the last 20 years, revolutionizing our understanding of their molecular etiology .…”
Section: Introductionmentioning
confidence: 99%